2016
DOI: 10.1089/ars.2016.6638
|View full text |Cite
|
Sign up to set email alerts
|

Oral Monomethyl Fumarate Therapy Ameliorates Retinopathy in a Humanized Mouse Model of Sickle Cell Disease

Abstract: In vivo ophthalmic imaging, electroretinography, and postmortem histological RNA and protein analyses were used to monitor retinal health and function in normal (HbAA) and sickle (HbSS) hemoglobin-producing mice over a one-year period and in additional HbAA and HbSS mice treated with MMF (15 mg/ml) for 5 months. Functional and morphological abnormalities and molecular hallmarks of oxidative stress/inflammation were evident early in HbSS retinas and increased in number and severity with age. Treatment with MMF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…39 Finally, a study from the Martin laboratory demonstrated that MMF can attenuate the retinopathy characteristic of sickle cell disease. 40 That study validated the Townes humanized sickle cell disease mouse as a model of Sickle retinopathy and reported that administration of MMF (in drinking water) beginning at 1 month improved the sickle retinopathy as evidenced by functional and structural retinal assessments. It is noteworthy that the onset of detectable retinal alterations in the sickle cell disease model was considerably later (4-7 months) and the severity significantly less than the rapid and fulminant photoreceptor cell loss observed in rd10 mice.…”
Section: Discussionmentioning
confidence: 77%
“…39 Finally, a study from the Martin laboratory demonstrated that MMF can attenuate the retinopathy characteristic of sickle cell disease. 40 That study validated the Townes humanized sickle cell disease mouse as a model of Sickle retinopathy and reported that administration of MMF (in drinking water) beginning at 1 month improved the sickle retinopathy as evidenced by functional and structural retinal assessments. It is noteworthy that the onset of detectable retinal alterations in the sickle cell disease model was considerably later (4-7 months) and the severity significantly less than the rapid and fulminant photoreceptor cell loss observed in rd10 mice.…”
Section: Discussionmentioning
confidence: 77%
“…Downstream, it induced CAMKK (Calcium/calmodulin-dependent protein kinase kinase 2) dependent activation of AMPK/SIRT-1 axis which also contributes to reduced inflammation. Several other studies have also reported on the HCAR2 receptor-dependent and independent anti-inflammatory effects of FAE in additional cell types including keratinocytes [31][32][33] and epithelial cells of the retina [34,35].…”
Section: Involvement Of Nrf2-dependent and Independent Mechanisms In mentioning
confidence: 91%
“…Because these initial reports of MMF's potential efficacy in protecting against retinal degeneration were conducted acutely, we decided to evaluate the effect of long-term administration of the compound (5 months administration of 15 mg/ml MMF in drinking water) in the humanized SCD model [34]. Importantly we found via high-pressure liquid chromatography (HPLC) and hematological analyses of peripheral blood that MMF treatment reduced sickle hemoglobin (HbS) content and white blood cell counts, and improved hematocrit, red blood cell number, and hemoglobin concentrations significantly in SCD mice.…”
Section: Retinal Degenerative Diseasesmentioning
confidence: 99%
“…83 The degree to which sickle red cells have deficient defense against oxidative damage has been associated with degree of anaemia. 84 Therefore, studies have been conducted and others are underway to explore the potential utility of anti-oxidant compounds, including arginine, alpha lipoic acid, omega 3 fatty acids, N-acetylcysteine, glutamine, Nrf2 activators, 85-88 haptoglobin, hemopexin 89 and others. Although studies in murine models have looked promising, 90,91 clinical studies have not yet shown definitive benefit to date, although some remain ongoing.…”
Section: Anti-oxidantsmentioning
confidence: 99%